Improving image quality and in-stent restenosis diagnosis with high-resolution “double-low” coronary CT angiography in patients after percutaneous coronary intervention - Wu, Wenjie; Zhan, Hefeng; Wang, Yiran; Ma, Xueyan; Hou, Jiameng; Ren, Lichen; Liu, Jie; Wang, Luotong; Zhang, Yonggao (Frontiers in Cardiovascular Medicine, 2024)
Objective: To investigate the image quality of a high-resolution, low-dose coronary CT angiography (CCTA) with deep learning image reconstruction (DLIR) and second-generation motion-correction algorithms, SnapShot Freeze 2(SSF2) algorithm and its diagnostic accuracy for in-stent restenosis (ISR) in patients after percutaneous coronary intervention (PCI), in comparison with standard-dose CCTA with high-definition mode reconstructed by adaptive statistical iterative reconstruction Veo algorithm (ASIR-V) and the first-generation motion-correction algorithm, SnapShot Freeze 1(SSF1). Methods: Patients after PCI and suspected of having ISR scheduled for high-resolution CCTA (randomly for 100kVp low-dose CCTA or 120kVp standard-dose) and invasive coronary angiography (ICA) were prospectively enrolled in this study. After the basic information pairing, total 105 patients were divided into the LD group (60 patients underwent 100kVp low-dose CCTA reconstructed with DLIR and SSF2) and the SD group (45 patients underwent 120kVp standard-dose CCTA reconstructed with ASIR-V and SSF1). Radiation and contrast medium doses, objective image quality including CT value, image noise (standard deviation), signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) for Aorta, left main artery (LM), left ascending artery (LAD), left circumflex artery (LCX), right coronary artery (RCA) of the two groups were compared. A 5-point scoring system was used for the overall image quality and stent appearance evaluation. Binary ISR was defined as an in-stent neointimal proliferation with diameter stenosis ≥ 50% to assess the diagnostic performance between the LD group and SD group with ICA as the standard reference. Results: The LD group achieved better objective and subjective image quality than the SD group even with 39.1% radiation dose reduction and 28.0% contrast media reduction. The LD group improved the diagnostic accuracy for coronary ISR to 94.2% from the 83.8% of the SD group on the stent-level and decreased the ratio of false positive cases by 19.2%. Conclusion: Compared with standard-dose CCTA with ASIR-V and SSF1, the high-resolution, low-dose CCTA with DLIR and SSF2 reconstruction algorithms further improves the image quality and diagnostic performance for coronary ISR at 39.1% radiation dose reduction and 28.0% contrast dose reduction.